Membangun Rumah Tangga Berbasis Moderasi Beragama: Strategi Pembinaan Calon Pengantin - Jihan Al Layyinah; Sukron Ma’mun; Abdul Khamid (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2026)
This study aims to examine in-depth the strategy for fostering prospective brides and grooms based on religious moderation, implemented by the Sidomukti Religious Affairs Office (KUA), Salatiga City. The main focus of this study is to identify key elements in the fostering process, assess its effectiveness, and explore various obstacles and challenges that arise during its implementation. The approach used is qualitative, with data collection methods including in-depth interviews, direct field observations, and analysis of related documents. The collected data are then analyzed using content analysis techniques to gain a comprehensive understanding. This study will also outline the importance of fostering prospective brides and grooms before marriage, and examine the concept and urgency of religious moderation within the context of such fostering. In addition, the study will critically review the strategies implemented by the Sidomukti KUA, Salatiga City, in order to realize religious moderation, along with the resulting impacts. The effectiveness of the program in increasing awareness and understanding of religious diversity among prospective brides and grooms will be a primary focus. The results of this study can provide constructive recommendations for the Sidomukti KUA, Salatiga City, to improve and enhance the quality of pre-marital guidance. Furthermore, these findings can also serve as a source of inspiration for other local governments in designing and developing programs for prospective brides and grooms that are adaptive, inclusive, and aligned with the values ​​of religious moderation.